The Relevance of Pedagogical Translation for the Development of Bilingual Education in Costa Rica - Hernández-Ching, Ruth Cristina (Revista Electrónica Educare, 2019)
The article reflects on bilingualism in Costa Rica in recent years in light of the latest versions of the Reports on the Costa Rican Public School Systems (2011, 2013, 2015 y 2017). Successful contributions of several national and international researches, where teaching translation as effective technique for developing communication skills is proposed, are discussed. Also, the article reviews major historical landmarks of translation in second language teaching. There are programs in the Ministry of Public Education (MEP), public and private colleges, schools and universities, but there is a tendency to associate the use of translation in teaching only with the grammatical method. Later studies could be oriented to compare the progress between populations that have acquired the language as a second language and have worked for a short period of time in a call center, in tourism, or in real life activities where they have to translate or interpret in real mode, compared to those that do not.